Cultura empreendedora e plano de negócios para o segmento odontológico: uma proposta de desenvolvimento de novas competências - Silva, Eliana Napoleão Cozendey da (2002)
The dentistry services, although the activities are submitted to a specific ethical code, is subdued to ali of the influences and consequences of a dynamic political and economie system. The dentist office can be compared to an arts-and-crafis industry and the products for saie are the dentistry procedures. this showing the need for a iogistic for the purchase of raw materiais and for negociation power vith the suppliers. The administrator, besides having updated tecbnical-scientific abilities, shouid create a competitive differential with the competitores, have competence to deal with interna! and external clients, resources and market, and methodoiogicai practices knowiedge information, which will be helpful on strategic decision making in a way to guarantee survival in a more competitive market. The quantitative exploratory research originated this dissertation in which the objective is to insert the entrepreneurship in the dentistry universe, concentrating on culture, idea validation, profile, and entrepreneur characteristics on the elaboration of a Business Plan. It also presents a simple BP, in a way to facilitate the comprehension of the importance as a fundamental part ofthe entrepreneur process, and it also approaches the necessity ofteaching the process and the paradigrn change about sustaining the Dental Surgeon s activity, bringing it to a reflection of teaching institutes and class entities about the necessity to motivate students and professionals. the entrepreneur attitude expanding the chance to become a succeeded, efticient, and ethicai DS inanager.